The Impact of Village Fund Efficiency on The Acceleration of Village Development After the Issuance of Minister of Finance Regulation Number 81 Of 2025: A Case Study Of Bandung Village, Banjar District, Pandeglang Regency - Nuryadin, Defi (Indonesian Journal of Social Science Research, 2025)
This study aims to analyze the impact of Village Fund budget efficiency on the acceleration of village development after the issuance of PMK Number 81 of 2025, with a case study in Bandung Village, Banjar District, Pandeglang Regency. This study uses a qualitative approach with a case study method. Data collection techniques were carried out through in-depth interviews with village officials and relevant stakeholders, as well as documentation studies of laws and regulations and village planning documents. Data analysis was carried out through data reduction, data presentation, and conclusion drawing stages. The results show that the Village Fund budget efficiency policy after PMK Number 81 of 2025 has encouraged a shift in the direction of village development from a dominance of physical spending towards more targeted and impact-oriented development. However, the acceleration of village development in Bandung Village has not yet been optimal. Budget efficiency is still understood administratively as spending reduction, so it has not fully improved the quality and speed of village development. The limited human resource capacity of village officials, weak impact-based performance indicators, and the risk of forming administrative economic institutions are the main inhibiting factors in realizing sustainable village development acceleration. This study concludes that the impact of Village Fund budget efficiency on the acceleration of village development after PMK Number 81 of 2025 is highly determined by the readiness of institutional capacity and village human resources.